2014
DOI: 10.1016/j.yqres.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Neotectonic evolution of the Brazilian northeastern continental margin based on sedimentary facies and ichnology,

Abstract: Quaternary post-Barreiras sediments are widespread along Brazil's passive margin. These deposits are well exposed in the onshore Paraíba Basin, which is one of the rift basins formed during the Pangean continental breakup. In this area, the post-Barreiras sediments consist of sandstones with abundant soft-sediment deformation structures related to seismicity contemporaneous with deposition. The trace fossilsThalassinoidesandPsilonichnusare found up to 38 m above modern sea level in sandstones dated between 60.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 65 publications
2
13
0
2
Order By: Relevance
“…The geochronology confirmed that sandy deposits are not associated with deposits of the underlying Barreiras Formation, whose age is Miocene to Pliocene times (Rossetti et al, 2013). Therefore, they are Post-Barreiras sediments of late Pleistocene age (Table 1), and these results are in line with other studies along the Brazilian coast (Tatumi et al, 2008;Rossetti et al, 2011;Gandini et al, 2014), including the same characteristic, which when collected in greater depth tend to be older.…”
Section: Characteristics Of Sedimentssupporting
confidence: 89%
See 2 more Smart Citations
“…The geochronology confirmed that sandy deposits are not associated with deposits of the underlying Barreiras Formation, whose age is Miocene to Pliocene times (Rossetti et al, 2013). Therefore, they are Post-Barreiras sediments of late Pleistocene age (Table 1), and these results are in line with other studies along the Brazilian coast (Tatumi et al, 2008;Rossetti et al, 2011;Gandini et al, 2014), including the same characteristic, which when collected in greater depth tend to be older.…”
Section: Characteristics Of Sedimentssupporting
confidence: 89%
“…The origin of these features varies between pedological processes forming sandy depressions (Moreau et al, 2006a;Oliveira et al, 2010;Schiavo et al, 2020). Also, by sedimentary deposition, forming the Post-Barreiras sediments (Tatumi et al, 2008;Rossetti et al, 2011;Gandini et al, 2014). In the literature, there are several pedological studies on sediments from the Barreiras Formation (Demattê et al, 1996;Moreau et al, 2006b;Cunha et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A unidade PB1 é pleistocênica tardia e inclui arenitos intercalados com argilitos e conglomerados, comumente associados a concreções de laterita. Esses depósitos registram processos fl uviais, de fl uxos gravitacionais subaéreos e, localmente, marinhos GANDINI et al, 2014). A unidade PB2 é principalmente holocênica, sendo constituída por sedimentos arenosos, em geral maciços.…”
Section: Fisiografi a E Contexto Geológicounclassified
“…Geologicamente, a unidade PB1 inclui arenitos intercalados com argilitos e conglomerados, comumente contendo fragmentos de concreções ferruginosas derivadas de paleossolos lateríticos que tipifi cam a discordância basal. Essa unidade é atribuída a ambientes fl uvial, fl uxos de detritos em leques aluviais e, localmente, marinho raso (ROSSETTI et al, 2012;GANDINI et al, 2014). A unidade PB2 sobrejacente é constituída por sedimentos arenosos, em geral maciços e pelo, menos em grande parte, gerada por processos eólicos (ROSSETTI et al, 2012).…”
Section: áRea De Estudounclassified